Simulating neuronal development: exploring potential mechanisms for central nervous system metastasis in acute lymphoblastic leukemia - Li, Ziping; Guo, Zhi; Xiao, Haitao; Chen, Xuexing; Liu, Wei; Zhou, Hao (Frontiers in Oncology, 2024)
Background: Acute lymphoblastic leukemia (ALL) is prone to metastasize the central nervous system (CNS), which is an important cause of poor treatment outcomes and unfavorable prognosis. However, the pathogenesis of CNS metastasis of ALL cells has not been fully illuminated. Recent reports have shed some light on the correlation between neural mechanisms and ALL CNS metastasis. These progressions prompt us to study the relationship between ALL central nervous metastasis and neuronal development, exploring potential biomarkers and therapeutic targets of CNS metastasis.Materials and methods: ALL central nervous system metastasis-and neuronal development-related differentially expressed genes (DEGs) were identified via analyzing gene expression datasets GSE60926 and GSE13715. Target prediction and network analysis methods were applied to assess protein-protein interaction networks. Gene Ontology (GO) terms and pathway enrichment for DEGs were assessed. Coexpressed differentially expressed genes (co-DEGs) coupled with corresponding predicted microRNAs (miRNAs) were studied as well. RT-PCR and flow cytometry were employed for the validation of key co-DEGs in primary ALL cells. Furthermore, ALL cells were treated with a VEGF inhibitor to block neuronal development and assess changes in the co-DEGs.We identified 216, 208, and 204 DEGs in ALL CNS metastasis specimens and neuronal development samples (GSE60926 & GSE13715). CD2, CD3G, CD3D, and LCK may be implicated in ALL CNS metastasis. LAMB1, MATN3, IGFBP3, LGALS1, and NEUROD1 may be associated with neuronal development. Specifically, four co-DEGs (LGALS1, TMEM71, SHISA2, and S100A11) may link ALL central nervous metastasis and neuronal development process. The miRNAs for each co-DEG could be potential biomarkers or therapeutic targets for ALL central nervous system metastasis, especially hsa-miR-22-3p, hsa-miR-548t-5p, and hsa-miR-6134. Besides, four co-DEGs (LGALS1, TMEM71, SHISA2, and S100A11) were validated in CNS-infiltrated ALL cells. The VEGF inhibitor demonstrated a suppressive effect on mRNA and protein expression of key co-DEGs.The bioinformatic survey and key genes validation suggest a possible correlation between ALL CNS metastasis and the neuronal development process.Simulating the neuronal development process might be a possible strategy for CNS metastasis in ALL. LGALS1, TMEM71, SHISA2, and S100A11 genes are promising and novel biomarkers and targets in ALL CNS metastasis.